Prevalence of middle mesial root canal in mandibular molars in an Iranian population: A micro-computed tomography study - Alireza Farhad; Mohsen Hasheminia; Ehsan Hekmatian; Vahid Mojiri (Wolters Kluwer Medknow Publications, 2024)
Background: Knowledge about the anatomic variations of the root canal system and their prevalence is necessary for clinicians to ideally clean the root canal system. The anatomic complexity of the root canal system is one of the reasons for its inadequate debridement, resulting in residual microorganisms and root canal treatment failure. The present study aimed to evaluate the prevalence of middle mesial root canals in mandibular molars in an Iranian population. Materials and Methods: The samples in the present descriptive/cross-sectional study consisted of mandibular first and second molars (n = 100, with 50 first and 50 s molars). A convenient sampling method was used to collect samples. The teeth were mounted in gypsum and scanned using a micro-computed tomography unit. The images were reconstructed with software, and the relevant checklist was completed by the observers. The data were analyzed with SPSS v26 using the Chi-squared test at a significance level of P < 0.05. Results: The prevalence of the middle mesial root canal in the present study was 36% for mandibular first molars and 22% for mandibular second molars, with an overall prevalence of 29%. The prevalence of the middle mesial root canal was not significantly different between the first and second mandibular molars (P = 0.12). The mean distance between the mesiobuccal and mesiolingual root canal orifices in the teeth with a middle mesial root canal was significantly higher than in those without the middle mesial root canal (P < 0.001). In addition, there was no significant difference in the prevalence of the middle mesial root canal between the teeth with and without the second distal root canal (P = 0.89). Conclusion: The prevalence of the middle mesial root canal in the studied population was 29%, which is significant clinically. In addition, the mean distance between the mesiobuccal and mesiolingual root canal orifices in teeth with a middle mesial root canal was higher than that in teeth without this root canal.